Application of a Nd:YAG laser to remove graffiti from Lioz limestone: influence of laser parameters (wavelength, fluence and number of pulses) and graffiti composition (Cadernos do Laboratorio Xeolóxico de Laxe. Revista de Xeoloxía Galega e do Hercínico Peninsular, 2021)
Recently laser ablation as a tool for cleaning heritage stones has experienced important improvements due to the mechanical contactless, the absence of residues, its gradualness and its selectivity. Once a laser equipment has been selected, optimization of the laser parameters (i.e. wavelength, fluence and number of pulses) has to be carried out. In this work, the influence of these parameters on the extraction of two compositionally different graffiti paints from the Portuguese limestone Lioz using a nanosecond Nd: YAG laser was evaluated. Unpainted and painted surfaces were treated with different wavelengths (infrared at 1064nm or ultraviolet at 355nm), fluences and number of pulses. Initially, the damage threshold was identified, and then, the most suitable conditions for the extraction of an alkyd blue graffiti and a polyethylene silver paint were detected. The resulting surfaces were evaluated by means of stereomicroscopy, spectrophotometry, roughness measurement and scanning electron microscopy.As a general result, after the optimization of the removal, differences were not identified for the results obtained by both wavelengths. However, the most influential factor in the efficacy was the graffiti paint composition. The silver paint was the most difficult graffiti to clean since after the laser application with the subsequent extraction of the aluminum sheets (inorganic pigment in this paint), a C-rich translucent layer was found on the surface. Although damage thresholds were established at 0.4 and 0.8 J.cm-2 for 355 and 1064 nm respectively, the fluences that allowed better results in terms of graffiti extraction were higher than these thresholds. The optimal fluences were different depending on the composition of paint: i) for blue paint, ultraviolet radiation (at 355 nm) achieved a satisfactory cleaning with 0.5 J.cm-2 and 10 pulses and infrared radiation (at 1064 nm) achieved it with 1.3 J.cm-2 and 25 pulses, and ii) for the silver paint, although the total extraction of the C-rich translucent layer was not achieved, the best efficiency levels were identified with 0.5 J.cm-2 and 5 pulses for 355 nm and 0.9 J.cm-2 and 5 pulses for 1064 nm. Therefore, the cleaning efficacy was influenced by the stone-graffiti interaction.